Tourism Advertising Using Specialized Mobile Applications and Its Impact on Increasing the Demand for the Services of Tourism Organizations - Nabil Mohemmed AL-Hazmi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This study aims to explore tourism advertising using specialized mobile applications and its impact on increasing tourism demand for the services of tourism organizations in Al-Kharj Governorate, the Kingdom of Saudi Arabia. In order to do so, the descriptive-analytical approach, which is consistent with the nature of the study, was used with a questionnaire form distributed to the targeted study sample of 150 forms. Different statistical methods have been used to test the study’s hypothesis. The study reached a wide range of results, the most important of which is the existence of an impact of tourism advertising by using specialized mobile applications on increasing demand for the services of travel and tourism organizations in Al-Kharj Governorate. Furthermore, a series of recommendations were provided, the most important of which is the need to catch up with technology and recent developments in the field of tourism advertising.